2017
DOI: 10.1002/ejp.1143
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effects of propranolol in the temporomandibular joint of female rats and its contribution to antinociceptive action

Abstract: β-Blockers have an anti-inflammatory effect on temporomandibular joint (TMJ) that contributes to its analgesic effect. The results of this work suggest that β-blockers can be used to treat the painful conditions of TMJ, especially when they are associated with an inflammatory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
2
23
0
1
Order By: Relevance
“…Because our data demonstrated that lipin-1 downregulation has an anti-inflammatory effect in the epidermis, we then verified whether the pharmacological inhibition of PAP1 activity had therapeutic effects on UVB-mediated inflammation. Propranolol displays antiinflammatory activity in cirrhosis 56 and murine temporomandibular joint 57 . Propranolol inhibited UVB-induced proinflammatory responses in the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Because our data demonstrated that lipin-1 downregulation has an anti-inflammatory effect in the epidermis, we then verified whether the pharmacological inhibition of PAP1 activity had therapeutic effects on UVB-mediated inflammation. Propranolol displays antiinflammatory activity in cirrhosis 56 and murine temporomandibular joint 57 . Propranolol inhibited UVB-induced proinflammatory responses in the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly adrenergic agonists are described to induce pain sensitization (Khasar et al, 1999(Khasar et al, , 2003Aley and Levine, 2003;Chen and Levine, 2005;Hucho et al, 2005). Accordingly, also blockers of beta adrenergic receptors have been shown to abrogate the onset of hyperalgesia (Zanelatto et al, 2018). But also pain-relieving activities of beta-adrenergic agonists have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We found a surprising dependence of the sensitizing activity on the stimulus context. In vitro and in vivo PKCe-activating substances including betaadrenergic agonists induce hyperalgesia if applied to a non-sensitized area (Khasar et al, 1999;Hucho et al, 2005Hucho et al, , 2006Hucho et al, , 2012Zanelatto et al, 2018). On the other hand in animal models, a 'sensitizing' stimulus could abrogate PKCe-dependent sensitization if applied to an already hyperalgesic tissue (Hucho et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…thepostero-inferior border of the left zygomatic arch was palpated and a needle of an insulin syringe was inserted immediately below this point and then advanced in the anterior direction until reaching the postero-lateral aspect of the condyle. Then, 50 µL of the carrageenan solution was injected into the left TMJ 2,5,19,20 . lllt procedure Low level laser therapy procedure was made transcutaneously in one contact point facing the central position of left TMJ, immediately after carrageenan injection while the animal is under anesthesia, using diode laser device ( Biolase epic X, USA) and deep tissue handpiece ( Biolase epic, USA), using wavelength 940 nm, spot radius 10mm, irradiation time 90 second and energy density for first experimental group was 171J/cm 2 and 74 J/cm 2 for the second experimental group, the procedure were repeated every 48 hours for the next seven days (four session of irradiation).…”
Section: Carrageenan Injectionmentioning
confidence: 99%
“…Comparison of head circumferences of all pairs in the last day of the experiment revealed non statistically significant differences between all pairs, indicating that the inflammation end in all groups (table 15). Induction of arthritis was made using the most common method used to evaluate the effects of different types of treatment protocols on inflammatory arthritis which is induction of arthritis using carrageenan solution injected directly into TMJ, carrageenan is polysaccharide obtained from sea weed, it have potent pro-inflammatory effect in animal joint when injected into the joint space 11 , previous studies had proof the carrageenan effectiveness in arthritis induction in TMJ of rats 19,20,24,25 . Pilot study revealed massive edema into TMJ area and decrease amount of food intake by rats suffering from arthritis comparing to normal rats and apparently that decrease in food consumption caused these rats look thinner, thus we made an attempt to evaluate these clinical findings caused by inducted TMJ arthritis and the effect of treatment protocol on head circumference changes caused by edema and weight changes caused by decrease food consumption due to loss proper function of inflamed TMJ.According to our knowledge there was no similar articles available that used head circumference and/or weight changes as clinical parameters for evaluating treatment protocol in induced arthritis, although several authors were report relations between similar parameters and pan-arthritis or joint arthritis (other than TMJ) in human studies as well as animal experimental studies including studies on rats, Vierboom et al, reported significant relation between weight changes and several diseases including arthritis in observational study in human 26 , Leech et al, found relation between lower extremities arthritis with weight and growth in human study 27 , Borb‫י‬ly et al, mentioned significant weight loss in mouse after induction of experimental autoimmunity arthritis 28 ,in the same way Hasan et al, reported similar weight loss in induced paw arthritis inSprague-Dawley rats using complete Freund's adjuvant 29 , identical weight loss secondary to induced arthritis were reported by several authors in Westar rats induced arthritis 21,22,30,32 , also there were several articles used body weight as parameter to assess TMJ function as secondary outcome depending on the fact that limited mouth opening would interfere with normal feeding such as the study of Angelo et al, and Richmond who did randomized clinical trial on Black Merino sheep temporomandibular joint andMiyamoto et al, who used body weight of mice as valuable index for evaluation TMJ diseases 33,35 .…”
Section: Weight Changesmentioning
confidence: 99%